(untitled) (Research, Society and Development, 2022)
In the context of road projects, the construction of bridges represents one of the biggest costs. Thus, the search for more economically viable solutions that reduce the use of materials and use them efficiently is essential. In this sense, the application of prestressing to such structures stands out, because this technique allows the maximum exploitation of the tensile strength of steel and the compressive strength of concrete. This work consists in the elaboration of a structural project of the multiple beams of the deck of a bridge using prestressed concrete. The design calculation ware developed using Mathcad 15.0 software – which, together with auxiliary software, allowed determining the forces acting on each beam of the deck. With these values, the most requested beam was determined, which was dimensioned in the rest of the project. Subsequently, the minimum prestressing effort that must act on the structure was determined. Then, through the positioning of the equivalent prestressing cable, the immediate and progressive prestressing losses were calculated. At the end of the project, the situations of the ultimate fatigue and bending limit states of the active reinforcement were verified and the service limit state of excessive deformations was also verified. The results allowed to conclude that the use of prestressing contributed to reduce the amount of steel used in the structure, besides reducing the deformations and also improving the behavior of the beam to the effects of fatigue.